Mitigating power quality disturbances in smart grid using FACTS - Yahia M. Esmail; Ali H. Kasem Alaboudy; M. S. Hassan; Gamal M. Dousoky (Institute of Advanced Engineering and Science, 2021)
Power quality (PQ) assurance is a vital part of electrical distribution networks. There are many advantages and benefits of improving PQ, especially in the modern/smart grid. Smart grid (SG) has a lot of complicated and sensitive electrical components (non-linear loads) in addition to renewable energy systems (wind-solar) that may also be a source of PQ disturbances. PQ problems harm personal life and national production. Static synchronous compensator (STATCOM) and unified power quality conditioner (UPQC) are among the fastest response flexible alternating current transmission systems (FACTS) installed in smart grids to mitigate power quality disturbances such as voltage fluctuations, sag, swell, and harmonics. In this research, STATCOM and UPQC are designed and simulated in MATLAB/Simulink to overcome PQ-related disruptions in smart grids. Accordingly, the differences between the proposed two solutions are highlighted across this research and renewable energy sources' reliability during faults. Therefore, the reader will be able to choose the appropriate FACTS devices. This study emphasizes the extent of the smart grid need for the FACTS. As per the given results of this study, STATCOM and UPQC have shown exemplary performance in the PQ improvement investigations conducted in the context of smart/modern grids.